2013
DOI: 10.1210/en.2013-1451
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Roles of Dmrt1 and Foxl2 in Sex Differentiation via Estrogen Production in Tilapia as Demonstrated by TALENs

Abstract: Transcription activator-like effector nucleases (TALENs) are a powerful approach for targeted genome editing and have been proved to be effective in several organisms. In this study, we reported that TALENs can induce somatic mutations in Nile tilapia, an important species for worldwide aquaculture, with reliably high efficiency. Six pairs of TALENs were constructed to target genes related to sex differentiation, including dmrt1, foxl2, cyp19a1a, gsdf, igf3, and nrob1b, and all resulted in indel mutations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(127 citation statements)
references
References 49 publications
7
118
0
Order By: Relevance
“…In males, Dmrt1 is a critical transcriptional regulator activating male-promoting genes (e.g., sox9 , sox8 ) while suppressing ovarian pathways ( foxl2 and rspo1 / wnt / β -catenin signalling) [Herpin and Schartl 2011a, b]. Dmrt1 interacts antagonistically with the female-specific transcription factor Foxl2 to influence cyp19a1a expression and control oestrogen production and gonadal fate in teleosts Li et al, 2013]. Under-or overexpression of either foxl2 or dmrt1 induces sexual cell fate reprogramming and gonadal sex reversal in mice and fish [Uhlenhaut et al, 2009;Matson et al, 2011;Li et al, 2013;Lindeman et al, 2015].…”
Section: Molecular Regulation Of Sex Change: Switches Triggers and mentioning
confidence: 99%
See 1 more Smart Citation
“…In males, Dmrt1 is a critical transcriptional regulator activating male-promoting genes (e.g., sox9 , sox8 ) while suppressing ovarian pathways ( foxl2 and rspo1 / wnt / β -catenin signalling) [Herpin and Schartl 2011a, b]. Dmrt1 interacts antagonistically with the female-specific transcription factor Foxl2 to influence cyp19a1a expression and control oestrogen production and gonadal fate in teleosts Li et al, 2013]. Under-or overexpression of either foxl2 or dmrt1 induces sexual cell fate reprogramming and gonadal sex reversal in mice and fish [Uhlenhaut et al, 2009;Matson et al, 2011;Li et al, 2013;Lindeman et al, 2015].…”
Section: Molecular Regulation Of Sex Change: Switches Triggers and mentioning
confidence: 99%
“…Dmrt1 interacts antagonistically with the female-specific transcription factor Foxl2 to influence cyp19a1a expression and control oestrogen production and gonadal fate in teleosts Li et al, 2013]. Under-or overexpression of either foxl2 or dmrt1 induces sexual cell fate reprogramming and gonadal sex reversal in mice and fish [Uhlenhaut et al, 2009;Matson et al, 2011;Li et al, 2013;Lindeman et al, 2015]. In gonochoristic and sex-changing fishes, cyp19a1a , foxl2, and dmrt1 expression is consistently sex-specific, depending on which gonadal phenotype is developing [Xia et al, 2007;Alam et al, 2008;Wu et al, 2008].…”
Section: Molecular Regulation Of Sex Change: Switches Triggers and mentioning
confidence: 99%
“…It is also an important laboratory model for understanding the developmental genetic basis of sex determination. The availability of monosex populations, together with the wholegenome sequence of Nile tilapia, has made it much easier to study the genes involved in sex determination (Soler et al 2010;M. H. Li et al 2013).…”
mentioning
confidence: 99%
“…sox9a and foxl2 were associated with the battle of sexes and the control of endogenous steroid hormone balance. Recently, cyp19a1a was found to be regulated by dmrt1 and its antagonistic gene, foxl2 (Li et al, 2013b), and foxl2 was confirmed as a cyp19a1a regulator. In the present study, the sex differentiation-related genes (Pcc-foxl2, nr5a1b, and sox9a) were significantly higher at 48 dph compared with other time points, which indicated that 48 dph was the turning point.…”
Section: Temporal Distribution Of the Target Genesmentioning
confidence: 99%